PERCEPTIONS OF YOUTH ABOUT PROCEDURAL AND DISTRIBUTIVE JUSTICE AND THEIR COOPERATION WITH POLICE - Noreen, Sidra; Tareen, Dr. Manan Khan; Bhutta, Dr. Muhammad Makkey; Tareen, Hannan Khan; Murtaza, Ghullam (The journal of contemporary issues in business and government, 2021)
The present study aimed to investigate as to how perceptions of the youth about procedural and distributive justice influence their cooperation with police. The study was conducted on students of the University of the Punjab, Lahore. The major objective of the study was to see whether or not perceptions about police legitimacy fostered cooperation of the youth with police for collaborative crime control. A survey of the University students was carried out and a structured questionnaire was used as a tool of data collection. Data were gathered from 111 students of the five randomly selected Departments of the University of the Punjab, Lahore. The findings of the present study showed that the perceptions of the students about procedural justice were significantly related with their intent to cooperate with police. The respondents’ judgments about the fairness of the police seemed to be important in promoting cooperation with police. This present research indicated that perceptions of police fairness were linked with social identity, which in turn was related with cooperation. Legitimacy judgments were the main drivers of cooperation. Overall, the findings of the present study showed that students had low schema about Police performance in procedural justice and they have negative notions about Police workforce for bringing harmony and stability in society.